Secondary modified silica sol as well as preparation method and application thereof
By secondary modification of the silicon sol, the modified silicon sol with high humidity strength, low residual strength and rapid collapse is formed with specific components, which solves the problem of cleaning the mold shell of light alloy castings and complex cavity castings, and achieves an efficient casting process and excellent casting quality.
Patent Information
- Application Number
- CN202411656660.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-25
AI Technical Summary
When existing modified silicon sols are treated with light alloy castings or castings with complex mold cavity, it is difficult to clean the mold shell, and traditional ordinary silicon sols are difficult to meet market demand.
By secondary modification of the silica sol, mPEG5K-silane and poloxamer 188 are used as primary modification components, aqueous acrylic emulsion and span 80 are used as secondary modification components to form a modified silica sol with high humidity strength, low residual strength and rapid rupture.
The high humidity strength of the casting back layer slurry is achieved, the residual strength of the mold shell is reduced, and the quick drying effect is improved. The shell can be quickly vibrated in subsequent sand cleaning, and there is very little sand powder residue, which improves the surface quality and production efficiency of the casting.
Smart Images

Figure CN119500972A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of modified silica sol, and particularly relates to a secondary modified silica sol and a preparation method and application thereof. Background Art
[0002] In investment casting technology, the production of the mold shell is a key step. After processes such as slurry dipping, sanding, drying, dewaxing, and high-temperature roasting, the mold shell will become very strong. However, this strong mold shell is extremely difficult to clean during the cleaning process, especially when dealing with light alloy castings or castings with complex cavities due to its large size and complex structure.
[0003] Currently, mold cleaning is often performed using vibrating or cleaning machines, but these are not ideal because the mold shells, after high-temperature firing, have become ceramicized and possess high strength. While conventional silica sols are widely used in investment casting, cleaning mold shells prepared using conventional silica sols remains challenging when processing certain casting types, such as light alloy castings or those with complex cavities. Furthermore, with process upgrades and optimizations, conventional silica sols are no longer able to meet market demand.
[0004] CN103962506A discloses a method for preparing a fiber-reinforced composite silica sol mold shell for investment casting, which comprises the following steps: 1. preparing a surface coating; 2. preparing a surface mold shell; 3. preparing a transition layer coating and a mold shell; and 4. preparing a backing coating. Mullite powder is added to the silica sol at a mass ratio of 2.2 to 3.0:1 between the refractory powder mullite powder in the backing coating and the silica sol to obtain a paste coating. Polypropylene fiber is added to the stirring paste coating at a mass ratio of 0.4 to 2.0% of the mass of the refractory powder mullite powder in the backing coating to uniformly disperse the polypropylene fiber. The silica sol is then added. The resulting mold shell has high wet strength and low residual strength. However, the subsequent introduction of polypropylene fiber during the slurry preparation process inevitably has a significant impact on overall stability. Furthermore, the operation process requires strict control of parameters such as the amount, order of addition, rate of addition, and stirring time, resulting in a complex process and an inability to guarantee production efficiency.
[0005] CN114669717A discloses a modified silica sol, a preparation method, and uses thereof. The raw materials of the modified silica sol include 95-100 parts of silica sol, 0.1-2 parts of polyvinyl alcohol, and 0.1-2 parts of hydroxypropyl methylcellulose in parts by weight. The preparation method of the modified silica sol includes: mixing the silica sol with polyvinyl alcohol to obtain a mixed solution A; mixing the mixed solution A with hydroxypropyl methylcellulose. The obtained modified silica sol has high adhesion, improves the wet strength of the casting slurry, resists cracking, and improves the surface quality of the casting. This modification is a one-time modification. Although the overall wet strength of the silica sol is greatly improved, the residual strength is not mentioned. In addition, the difficulty of subsequent sand cleaning for this one-time modified silica sol remains unknown.
[0006] Therefore, for the existing modified silica sols, how to develop a modified silica sol that can improve the wet strength of the back layer slurry of the casting, reduce the residual strength of the mold shell, improve the quick drying effect, and quickly vibrate the shell during subsequent sand cleaning, with very little sand powder residue, while effectively maintaining the quality and performance of the material itself, is still a technical problem that needs to be solved urgently in this field. Summary of the Invention
[0007] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a secondary modified silica sol and a preparation method and application thereof. By secondary modification of the silica sol, the viscosity of the obtained secondary modified silica sol is increased and the adhesion is high. The wet strength of the casting back layer slurry containing the secondary modified silica sol is high, the collapsibility of the investment casting back layer is improved, the residual strength of the shell is reduced, and the quick-drying effect is strong. In the subsequent sand cleaning, the shell can be quickly vibrated, and very little sand powder remains, which can effectively maintain the quality and performance of the material itself, so that the surface quality of the casting is good, greatly improving production efficiency and saving manufacturing costs.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a secondary modified silica sol, wherein the raw materials of the secondary modified silica sol include silica sol, a primary modified component, a secondary modified component and water;
[0010] The primary modification component includes mPEG5K-silane and poloxamer 188;
[0011] The secondary modification component includes water-based acrylic emulsion and Span 80.
[0012] The raw materials for the secondary modified silica sol provided by the present invention include silica sol, a primary modifying component, a secondary modifying component, and water. The silica sol is the core component of the modified silica sol. In investment casting, the silica sol provides good adhesion and a certain strength. It also has good thermal stability at high temperatures, helping to maintain the integrity of the backing layer structure.
[0013] The primary modification components include mPEG5K-silane and poloxamer 188. mPEG5K-silane, a primary modification coupling agent, is a silane coupling agent containing polyethylene glycol (PEG) chains. The silane groups of mPEG5K-silane react with silicate groups in the silica sol to form stable silicon-oxygen bonds, strengthening the cross-linked structure of the material and enhancing its thermal stability and mechanical strength. Furthermore, the introduction of PEG chains into the mPEG5K-silane improves the material's wettability and dispersibility, contributing to increased slurry uniformity and adhesion, and ensuring more uniform spreading on the mold surface. Poloxamer 188, a primary modification stabilizer, is a nonionic surfactant with temperature-sensitive gel-sol transition properties. In investment casting, it can act as a stabilizer and thickener, helping to adjust the viscosity of the silica sol, making it easier to coat and form. Furthermore, the thermal sensitivity of poloxamer 188 may also help control the collapse of the backing material during the casting process.
[0014] The secondary modification components include water-based acrylic emulsion and Span 80. The secondary modification stage further enhances the performance of the material. The water-based acrylic emulsion, as a secondary modifier, is a polymer dispersion. In the backing material of investment casting, the water-based acrylic emulsion can provide additional adhesion and mechanical strength, and improve the water resistance and chemical resistance of the material through its polymer network. Span 80, as a secondary modification promoter, is a non-ionic surfactant commonly used as an emulsifier and dispersant. It can improve the dispersibility of silica sol and other components and prevent precipitation or aggregation of the material during storage and use. Therefore, the modification at this stage not only enhances the physical properties of the material, but also improves the adhesion and chemical resistance of the material through the form of a physical interpenetrating network, providing a guarantee for chemical medium resistance during the casting process.
[0015] In the investment casting process, the performance of the backing material is crucial, affecting not only the surface quality of the casting but also the efficiency of the casting process. The secondary modified silica sol provided by the present invention is modified by using the primary and secondary modified components of the above-mentioned specific components. The two modifications can work synergistically to jointly construct a modified silica sol system with high wet strength, low residual strength, and rapid collapse. In the backing slurry, this synergistic effect not only improves the adhesion and mechanical strength of the material in a wet state, ensuring formability and stability during the casting process; at the same time, due to the pyrolysis properties of mPEG5K-silane and water-based acrylic emulsion, the material reduces residual strength at high temperatures, achieves rapid collapse, and reduces adhesion to the casting. In particular, the temperature sensitivity of Poloxamer 188 further optimizes the collapse behavior, allowing the backing material to disintegrate in a timely manner during the casting process, avoiding unnecessary damage to the casting. The surface activity of Span80 reduces the interfacial tension between the silica sol and other components, improves the material's dispersibility, improves the material's spreadability on the mold surface, and enhances the uniformity and adhesion of the coating.
[0016] Therefore, the above-mentioned comprehensive effects can be achieved. Each of the above-mentioned components has a decisive influence on the performance of the final material. Chemical cross-linking enhances the cohesion and adhesion of the material, the physical interpenetrating network improves the adhesion and mechanical strength of the material, the surface activity regulation improves the spreadability and dispersibility of the material, and the temperature sensitivity provides controllability for the collapse behavior of the material. The synergistic effect of these interactions enables the modified silica sol to exhibit excellent performance in investment casting, including high wet strength, low residual strength and rapid collapse ability. The preparation of this material not only improves the efficiency of the casting process and the quality of the castings, but also has good environmental adaptability and process compatibility, providing new possibilities for the development of investment casting technology.
[0017] Preferably, the raw materials of the secondary modified silica sol include the following components in parts by weight:
[0018] 88-96.5 parts by weight of silica sol;
[0019]
[0020] The amount of the silica sol can be 88 parts by weight, 89 parts by weight, 90 parts by weight, 92 parts by weight, 94 parts by weight, 96 parts by weight, or 96.5 parts by weight.
[0021] The amount of the mPEG5K-silane can be 1 part by weight, 1.5 parts by weight, 2 parts by weight, 2.5 parts by weight, 3 parts by weight, 3.5 parts by weight or 4 parts by weight.
[0022] The amount of Poloxamer 188 can be 0.5 parts by weight, 0.6 parts by weight, 0.7 parts by weight, 0.8 parts by weight, 0.9 parts by weight or 1 part by weight, etc.
[0023] The amount of the aqueous acrylic emulsion can be 1 part by weight, 1.5 parts by weight, 2 parts by weight, 2.5 parts by weight, 3 parts by weight, 3.5 parts by weight or 4 parts by weight.
[0024] The amount of Siban 80 can be 0.5 parts by weight, 0.6 parts by weight, 0.7 parts by weight, 0.8 parts by weight, 0.9 parts by weight or 1 part by weight.
[0025] The amount of water used can be 0.5 parts by weight, 0.7 parts by weight, 0.9 parts by weight, 1.1 parts by weight, 1.3 parts by weight, 1.5 parts by weight, 1.7 parts by weight or 1.9 parts by weight, etc.
[0026] Preferably, the solid content of the silica sol is 25-35%, for example, 25%, 27%, 29%, 31%, 33% or 35%.
[0027] Preferably, the pH value of the silica sol is 9.5 to 10.5, for example, 9.5, 9.7, 9.9, 10.1, 10.3 or 10.5.
[0028] In a second aspect, the present invention provides a method for preparing the secondary modified silica sol as described in the first aspect, the preparation method comprising the following steps:
[0029] (1) mixing poloxamer 188 and a portion of water to obtain liquid A;
[0030] Mix Span 80 and the remaining water to obtain liquid B;
[0031] (2) adding the solution A obtained in step (1) to the silica sol and mixing, cooling and then adding mPEG5K-silane to react to obtain a primary modified silica sol;
[0032] (3) adding the solution B obtained in step (1) to the primary modified silica sol obtained in step (2) and mixing them, heating the mixture and then adding the aqueous acrylic emulsion to react to obtain the secondary modified silica sol.
[0033] If the order of steps (2) and (3) is reversed, i.e., the primary modification is performed using aqueous acrylic emulsion and Span 80, and the secondary modification is performed using mPEG5K-silane and poloxamer 188, the modified silica sol with high disintegrability for the investment casting backing layer cannot be obtained, resulting in extremely poor performance and stability.
[0034] Preferably, the amount of water in step (1) is 0.25 to 1 part by weight, such as 0.25 part by weight, 0.5 part by weight, 0.75 part by weight or 1 part by weight.
[0035] Preferably, the mixing of Poloxamer 188 and part of the water in step (1) and the mixing of Span 80 and the remaining part of the water in step (1) are both carried out under stirring conditions.
[0036] Preferably, the stirring speed is 200-300 rpm, for example, 200 rpm, 210 rpm, 220 rpm, 230 rpm, 240 rpm, 250 rpm, 260 rpm, 270 rpm, 280 rpm, 290 rpm or 300 rpm.
[0037] Preferably, the mixing temperature of mixing Poloxamer 188 and part of the water in step (1) and mixing Span 80 and the remaining part of the water in step (1) are each independently 20 to 40°C, for example, 20°C, 22°C, 24°C, 26°C, 28°C, 30°C, 32°C, 34°C, 36°C, 38°C or 40°C, and more preferably room temperature.
[0038] Preferably, the mixing in step (2) is carried out under stirring conditions.
[0039] Preferably, the stirring speed is 200-300 rpm, for example, 200 rpm, 210 rpm, 220 rpm, 230 rpm, 240 rpm, 250 rpm, 260 rpm, 270 rpm, 280 rpm, 290 rpm or 300 rpm.
[0040] Preferably, the mixing temperature in step (2) is 20-40°C, for example, 20°C, 22°C, 24°C, 26°C, 28°C, 30°C, 32°C, 34°C, 36°C, 38°C or 40°C, and more preferably room temperature.
[0041] Preferably, the mixing time in step (2) is 1 to 2 hours, for example, 1 hour, 1.1 hours, 1.2 hours, 1.3 hours, 1.4 hours, 1.5 hours, 1.6 hours, 1.7 hours, 1.8 hours, 1.9 hours or 2 hours.
[0042] Preferably, the temperature of the system after cooling in step (2) is 1 to 5°C, for example, 1°C, 1.5°C, 2°C, 2.5°C, 3°C, 3.5°C, 4°C, 4.5°C or 5°C.
[0043] Preferably, the reaction temperature in step (2) is 1-5°C, for example, 1°C, 1.5°C, 2°C, 2.5°C, 3°C, 3.5°C, 4°C, 4.5°C or 5°C.
[0044] As a preferred technical solution of the present invention, the main reason for lowering the temperature and controlling the reaction temperature after the mixing in step (2) is to prevent premature polymerization of mPEG5K-silane, control the stability of the silica sol, optimize the compatibility of mPEG5K-silane and the silica sol, and ensure the uniformity of the reaction. Specifically:
[0045] First, prevent premature polymerization of mPEG5K-silane: mPEG5K-silane is a highly reactive compound that easily undergoes polymerization reactions at high temperatures. Lowering the temperature can slow down the rate of this polymerization reaction, thereby ensuring that mPEG5K-silane can be evenly dispersed in the silica sol and avoiding uneven polymerization caused by local overheating. If the temperature is not lowered, impurities may precipitate during the reaction, affecting the dissolution efficiency of the reactants and thus affecting the preparation of the formula.
[0046] Second, control the stability of silica sol: Silica sol may undergo structural changes at high temperatures, affecting its stability. By lowering the temperature, the stability of silica sol can be maintained, avoiding colloid aggregation or precipitation caused by excessively high temperatures.
[0047] Third, optimize the compatibility of mPEG5K-silane and silica sol: At lower temperatures, the compatibility between mPEG5K-silane and silica sol is better, which helps to form a uniform mixture and improve the uniformity and consistency of the modified silica sol.
[0048] Fourth, ensure the uniformity of the reaction: carrying out the reaction at a lower temperature can ensure the uniform distribution of mPEG5K-silane in the silica sol and avoid uneven reaction caused by local overheating.
[0049] Preferably, the reaction time of step (2) is 1 to 2 h, for example, 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h or 2 h.
[0050] Preferably, the mixing in step (3) is carried out under stirring conditions.
[0051] Preferably, the stirring speed is 200-300 rpm, for example, 200 rpm, 210 rpm, 220 rpm, 230 rpm, 240 rpm, 250 rpm, 260 rpm, 270 rpm, 280 rpm, 290 rpm or 300 rpm.
[0052] Preferably, the mixing temperature in step (2) is 20-40°C, for example, 20°C, 22°C, 24°C, 26°C, 28°C, 30°C, 32°C, 34°C, 36°C, 38°C or 40°C, and more preferably room temperature.
[0053] Preferably, the mixing time in step (2) is 1 to 2 hours, for example, 1 hour, 1.2 hours, 1.4 hours, 1.6 hours, 1.8 hours or 2 hours.
[0054] Preferably, the temperature of the system after heating in step (3) is 60-70°C, for example, 60°C, 62°C, 64°C, 66°C, 68°C or 70°C.
[0055] Preferably, the reaction temperature in step (3) is 60-70°C, for example, 60°C, 62°C, 64°C, 66°C, 68°C or 70°C.
[0056] As a preferred technical solution of the present invention, in step (4), the main reasons for increasing the temperature and controlling the reaction temperature are to promote the dissolution and dispersion of the aqueous acrylic emulsion, enhance the emulsification effect of Span 80, optimize the formation of the physical interpenetrating network, increase the reaction rate and ensure the thermal stability of the material. Specifically:
[0057] First, it promotes the dissolution and dispersion of water-based acrylic emulsions: Water-based acrylic emulsions dissolve and disperse more easily at higher temperatures. By increasing the temperature, the emulsion can be evenly distributed in the modified silica sol, improving the uniformity and consistency of the final product.
[0058] Second, it enhances the emulsification effect of Span 80: As an emulsifier, Span 80 has better emulsification effect at higher temperatures; increasing the temperature helps Span 80 better exert its emulsification effect and improve the stability and dispersibility of the modified silica sol.
[0059] Third, optimize the formation of a physical interpenetrating network: At a reaction temperature of 60-70°C, the polymer in the aqueous acrylic emulsion is more likely to form a physical interpenetrating network with the silica sol. This interpenetrating network can enhance the mechanical strength and adhesion of the modified silica sol and improve its performance in the casting process.
[0060] Fourth, improve the reaction rate: At higher temperatures, molecular movement is more active, which is conducive to increasing the reaction rate between water-based acrylic emulsion and silica sol, shortening the reaction time and improving production efficiency.
[0061] Fifth, ensure the thermal stability of the material: Conducting the reaction at a reaction temperature of 60-70°C can ensure that the modified silica sol has good thermal stability in the subsequent high-temperature casting process, avoiding performance degradation due to temperature changes.
[0062] Preferably, the reaction time of step (3) is 1 to 2 h, for example, 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h or 2 h.
[0063] In a third aspect, the present invention provides an investment casting backing layer slurry, wherein the investment casting backing layer slurry comprises the secondary modified silica sol as described in the first aspect.
[0064] In a fourth aspect, the present invention provides a use of the investment casting backing layer slurry as described in the first aspect in investment casting.
[0065] Compared with the prior art, the present invention has the following beneficial effects:
[0066] The raw materials of the secondary modified silica sol provided by the present invention include silica sol, a primary modified component, a secondary modified component and water, the primary modified component includes mPEG5K-silane and poloxamer 188, and the secondary modified component includes water-based acrylic emulsion and Span 80. By adopting the above-mentioned specific raw materials to perform secondary modification on the silica sol, the obtained secondary modified silica sol has high viscosity and high adhesion, the casting back layer slurry containing the secondary modified silica sol has high wet strength, improves the collapsibility of the investment casting back layer, reduces the residual strength of the mold shell, and has a strong quick-drying effect. In the subsequent sand cleaning, the shell can be quickly vibrated with very little sand powder residue, effectively maintaining the quality and performance of the material itself, so that the surface quality of the casting is good, the production efficiency is greatly improved, and the manufacturing cost is saved. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] Figure 1 This is a scanning electron microscope image of the secondary modified silica sol provided in Example 6 at 100K magnification;
[0068] Figure 2 A scanning electron microscope image of the secondary modified silica sol provided in Example 6 at 50K magnification;
[0069] Figure 3 This is a scanning electron microscope image of unmodified silica sol at 100K magnification;
[0070] Figure 4 This is a scanning electron microscope image of unmodified silica sol at 50K magnification. DETAILED DESCRIPTION
[0071] The technical solution of the present invention is further described below by way of specific embodiments. It should be understood by those skilled in the art that the embodiments are merely to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0072] Unless otherwise specified, the raw materials involved in the following examples and comparative examples are conventional materials in the art and can be purchased commercially. In particular, information on some of the raw materials involved is as follows:
[0073] (1) Silica sol: solid content 30%, purchased from Guangdong Huierte Nanotechnology Co., Ltd., brand S-1430 silica sol;
[0074] (2) Water-based acrylic emulsion: purchased from Nanjing Baiju Chemical Co., Ltd.
[0075] Examples 1 to 8 and Comparative Examples 1 to 4
[0076] Examples 1 to 8 and Comparative Examples 1 to 4 respectively provide a modified silica sol, the amounts of the components contained therein are shown in Table 1. In Table 1, the amount range of each component is "parts by weight";
[0077] Table 1
[0078]
[0079]
[0080] The preparation methods of the modified silica sols provided in Examples 1 to 8 and Comparative Examples 1 to 4 include the following steps:
[0081] (1) Add 1 / 2 of the total amount of water to a container, stir at a speed of 250 rpm, add Poloxamer 188, and continue stirring at room temperature until it is completely dissolved to obtain Liquid A;
[0082] Add the remaining water to another container, stir at 250 rpm, add Span 80, and continue stirring at room temperature until completely dissolved to obtain liquid B;
[0083] (2) Add silica sol to the container, stir at a speed of 250 rpm, add liquid A obtained in step (1) at a drop rate of 100 mL / h, continue stirring at room temperature for 1.5 h until completely dissolved, reduce the temperature to 2° C., then add mPEG5K-silane at a drop rate of 50 mL / h, and stir at 2° C. for 1.5 h to obtain the primary modified silica sol;
[0084] (3) Liquid B obtained in step (1) was added to the primary modified silica sol obtained in step (2) at a drop rate of 100 mL / h, and the mixture was stirred at a speed of 250 rpm and room temperature for 1.5 h until it was completely dissolved. The temperature was raised to 65° C., and the aqueous acrylic emulsion was added at a drop rate of 100 mL / h. The mixture was stirred and reacted at 65° C. for 1.5 h to obtain the secondary modified silica sol.
[0085] Comparative Example 5
[0086] A secondary modified silica sol, the preparation method of which comprises the following steps:
[0087] (1) Add 1 / 2 of the total amount of water to a container, stir at a speed of 250 rpm, add Poloxamer 188, and continue stirring at room temperature until it is completely dissolved to obtain Liquid A;
[0088] Add the remaining water to another container, stir at 250 rpm, add Span 80, and continue stirring at room temperature until completely dissolved to obtain liquid B;
[0089] (2) adding silica sol to a container, stirring at a speed of 250 rpm, adding liquid B obtained in step (1) at a drop rate of 100 mL / h, stirring continuously at a speed of 250 rpm and room temperature for 1.5 h until completely dissolved, raising the temperature to 65° C., and then adding aqueous acrylic emulsion at a drop rate of 100 mL / h, stirring and reacting at 65° C. for 1.5 h to obtain the primary modified silica sol;
[0090] (3) Liquid A obtained in step (1) was added to the primary modified silica sol obtained in step (2) at a dropwise rate of 100 mL / h, and the mixture was stirred at room temperature for 1.5 h until completely dissolved. The temperature was lowered to 2°C, and mPEG5K-silane was added at a dropwise rate of 50 mL / h. The mixture was stirred and reacted at 2°C for 1.5 h to obtain the secondary modified silica sol.
[0091] Performance testing:
[0092] (1) Quick drying time between mold layers: It is measured by moisture content. After the mold slurry is dry, start recording the time. When the water content on the mold surface is 5-10%, or the mold no longer loses water (crystallization water), it indicates that the mold has been dried. Then, the drying time of each layer is counted to calculate the quick drying time between the mold layers.
[0093] (2) Viscosity: The viscosity of the modified silica sol was measured by a viscometer.
[0094] (3) Wet strength of the shell: The JB / T13038-2017 method is used for testing, and a wet strength greater than 6 is considered good.
[0095] (4) Residual strength of the shell: The JB / T13038-2017 method is used for testing; a residual strength below 3 is considered to be good; in addition, the wet strength is much greater than the residual strength, and is a multiple type. At this time, the sand cleaning is the best.
[0096] (5) Sand cleaning effect of castings: Modified silica sol and refractory material (mullite powder, purchased from Guanxing Guwang Technology Co., Ltd., specification is 25kg / bag) are mixed in a mass ratio of 1:2 to prepare the back layer slurry. After casting the vibration shell, the sand cleaning and residual sand particles of the workpiece are observed. The judgment standard is the mortar residual rate.
[0097] The modified silica sols provided in Examples 1 to 8 and Comparative Examples 1 to 5 were tested according to the above test method. The test results are shown in Table 1:
[0098] Table 1
[0099]
[0100]
[0101] According to the data in Table 1, we can see that:
[0102] Too much silica sol (Example 8) will lead to poor modification effect, resulting in excessive residual strength, making subsequent sand cleaning difficult. Moreover, since the silica sol modified with mPEG5K-silane can effectively increase the quick-drying time, improve the overall wet strength and reduce the residual strength, the use of a relatively excessive amount of water-based acrylic emulsion will have a corresponding impact on the quick-drying time and the wet strength of the shell.
[0103] The primary modification was performed with aqueous acrylic emulsion and Span 80, followed by secondary modification with mPEG5K-silane and Poloxamer 188. The modification order was reversed, but it was found that the modification effect became extremely poor and the modification failed. Therefore, the modification order is crucial.
[0104] The preparation of modified silica sols involves multiple interactions, including chemical crosslinking, physical interpenetrating networks, surface activity regulation, and temperature sensitivity. These interactions create a superior backing layer material, capable of delivering high green strength, low residual strength, and rapid collapse in investment casting. Only by introducing each component in a specific and orderly manner, according to specific ratios, can the modified silica sol achieve the high performance required for investment casting backing layer materials.
[0105] In addition, the secondary modified silica sol and the unmodified silica sol provided in Example 6 were tested using a scanning electron microscope. The scanning electron microscope image of the secondary modified silica sol provided in Example 6 at 100K magnification was as follows: Figure 1 As shown, the scanning electron microscope image of the secondary modified silica sol provided in Example 6 at 50K magnification is as follows Figure 2 As shown, the scanning electron microscope image of the unmodified silica sol at 100K is shown in FIG. Figure 3As shown, the scanning electron microscope image of the unmodified silica sol at 50K magnification is as follows Figure 4 As shown;
[0106] from Figures 1 and 2 and Figures 3 and 4 The comparison shows that: Figures 3 and 4 The distribution of unmodified silica sol is uniform, while Figures 1 and 2 The surface of the modified silica sol provided in Example 6 has many grooves and layers.
[0107] The applicant states that while the present invention, through the aforementioned embodiments, illustrates a contamination-resistant and wetting-resistant hydrophilic-hydrophobic composite membrane for membrane distillation, its preparation method, and its application, the present invention is not limited to the aforementioned process steps, nor does it necessarily rely on the aforementioned process steps for implementation. Persons skilled in the art will appreciate that any improvements to the present invention, equivalent substitutions for the raw materials used, additions of auxiliary components, and selection of specific methods, etc., fall within the scope of protection and disclosure of the present invention.
Claims
1. A secondary modified silica sol, characterized in that: The raw materials of the secondary modified silica sol include silica sol, primary modified components, secondary modified components and water; The primary modification component includes mPEG5K-silane and poloxamer 188; The secondary modification component includes water-based acrylic emulsion and Span 80.
2. The secondary modified silica sol according to claim 1, characterized in that: The raw materials of the secondary modified silica sol include the following components in parts by weight:
3. The secondary modified silica sol according to claim 1 or 2, characterized in that: The solid content of the silica sol is 25-35%; Preferably, the pH value of the silica sol is 9.5-10.
5.
4. A method for preparing the secondary modified silica sol according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) mixing poloxamer 188 and part of water to obtain liquid A; Mix Span 80 and the remaining water to obtain liquid B; (2) adding the solution A obtained in step (1) to the silica sol and mixing, and then adding mPEG5K-silane to react after cooling to obtain a primary modified silica sol; (3) adding the solution B obtained in step (1) to the primary modified silica sol obtained in step (2) to mix, and then adding the aqueous acrylic emulsion to react after heating to obtain the secondary modified silica sol.
5. The preparation method according to claim 4, characterized in that: The mixing of Poloxamer 188 and part of the water and the mixing of Span 80 and the remaining part of the water in step (1) are both carried out under stirring; Preferably, the stirring speed is 200-300 rpm.
6. The preparation method according to claim 4 or 5, characterized in that: The mixing in step (2) is carried out under stirring; Preferably, the stirring speed is 200-300 rpm; Preferably, the mixing temperature in step (2) is 20 to 40° C., more preferably room temperature; Preferably, the mixing time in step (2) is 1 to 2 hours; Preferably, the temperature of the system after cooling in step (2) is 1 to 5°C.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The reaction temperature of step (2) is 1-5°C and the reaction time is 1-2h.
8. The preparation method according to any one of claims 4 to 7, characterized in that: The mixing in step (3) is carried out under stirring; Preferably, the stirring speed is 200-300 rpm; Preferably, the mixing temperature in step (2) is 20 to 40° C., more preferably room temperature; Preferably, the mixing time in step (2) is 1 to 2 hours; Preferably, the temperature of the system after heating in step (3) is 60-70°C; Preferably, the reaction temperature in step (3) is 60-70° C. and the reaction time is 1-2 h.
9. An investment casting backing slurry, characterized in that: The investment casting backing layer slurry comprises the secondary modified silica sol as claimed in any one of claims 1 to 3.
10. Use of the investment casting backing layer slurry as claimed in claim 9 in investment casting.
Citation Information
Patent Citations
Preparation method of fiber reinforced compound silica sol shell for investment casting
CN103962506A
Cited By
Precision casting back layer and / or surface layer universal modified silica sol and preparation method and application thereof
CN120394766A
A precision casting back layer and / or face layer universal modified silica sol, and a preparation method and application thereof
CN120394766B